(untitled) (Revista Espinhaço, 2017)
This article is the result of a reflection on the possible ways to relate the territorial management where three of the municipalities of Minas Gerais are located, which received the seal of World Cultural Heritage granted by the United Nations Educational, Scientific and Cultural Organization (UNESCO). Two of these municipalities are also included in the proposal to create the Quadrilátero Ferrífero Geopark, in the spatial context of the Serra do Espinhaço Biosphere Reserve (RBSE), a seal granted by the same international body. From the survey on the management mechanisms of the RBSE region, a collaborative system between cultural and natural sites is proposed, so that this management can be carried out in a more integrated and efficient way, in order to give more visibility to the historical-cultural heritage aiming at the conservation and development of the region.